Pengaruh Variabel Sosioekonomi dan Lingkungan Terhadap Prevalensi Stunting Secara Spasial di Provinsi Nusa Tenggara Timur Tahun 2023 - Wisly Ryan Eliezer; Natasya Alwanti (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
Stunting is one of the Government of Indonesia's priority issues. As a region of Central Indonesia, all districts/cities in East Nusa Tenggara have high and very high stunting prevalence. Environmental conditions in East Nusa Tenggara need attention as one of the causes of stunting along with other socioeconomic variables. Therefore, this study aims to provide an overview of the variables that influence stunting in districts/cities in East Nusa Tenggara Province. The Spatial Autoregressive Model method was chosen to accommodate the presence of spatial autocorrelation in the model. in the model so that the results obtained that the percentage of households with access to proper drinking water, the percentage of women who marry early, the percentage of toddlers with complete basic immunization, per capita expenditure on food, population density, and ground level ozone in districts/cities in East Nusa Tenggara in 2023.